Semantic Domain of Hand Activity to Hold in Mandailing Language - Anharuddin Hutasuhut; Waridah Waridah (Budapest International Research and Critics University, 2019)
This research is based on research data in the form of lexemes or words that express the concept of hand activity in Mandailing language. The data of this study are a number of Mandailing language lexemes which contain the meaning of hand activity. All data obtained is recorded and ordered. The data that has been recorded on the data card is classified based on the similarity of the lexical semantic component. The lexemes which stated the hand activity in Mandailing language which had been inventoried were eighty-five lexemes. These lexemes are classified based on the components of the meaning they have so as to form groups or more sub-domain specific meanings. From the study, there were twenty groups of sub-domain meanings based on the purpose of the activity, namely (1) holding, (2) touching, (3) taking, (4) carrying, (5) laying, (6) throwing, (7) giving, (8) receiving, (9) opening, (10) closing, (11) pulling, (12) pushing, (13) hurting, (14) destroying, (15) rolling, (16) calling out, (17) expelling, (18) ) blocking, (19) greeting, and (20) pointing.